The effect of organizational justice on the quality of work life through organizational commitment as a mediating variabel - Purwanti Purwanti; Sinta Sundari Heriyanti (Jurnal Mantik, 2024)
In this research is discussed the influence of organizational justice on organizational commitment through the quality of work life as a mediating variable among employees of PT Aristek Highpolymer. The research methodology used in this study is quantitative with a causal associative approach. Primary data was collected through questionnaires using the Likert scale. The sample consists of 75 employees selected from a population of 295 employees using the Slovin formula. The data was analyzed using validity tests, reliability tests, inner model tests, and hypothesis tests using SmartPLS 0.4. The results show that organizational justice has a positive influence on organizational commitment. However, there is no relationship between the quality of work life and organizational commitment. Employees who perceive organizational justice in their company are more motivated to work well and diligently, leading to an improvement in the quality of their work. This study emphasizes the importance of developing new ways of managing human resources, including organizational justice and organizational commitment, to make human resources a competitive advantage for the company